Risk and decision analysis in projects - Schuyler, John R., 1950- (Project Management Institute, 2001)
Annotation Schuyler has over 25 years of experience in economic evaluation, training, and management. Here he presents a text on decision analysis (DA), the discipline which aids decision makers in making sound choices under conditions of uncertainty. Coverage includes an overview of the concept of decision analysis; how DA applies to project risk management; a general problem-solving process; details about project modeling; the use of probability distributions for uncertain inputs; some emerging techniques including critical chain project management, optimization, and expert systems; and a brief tutorial about probability rules. The text is based on articles contributed by the author to the magazine, PM Network, from 1992 through 2000. Written for project managers. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Keywords: Decision making.; Uncertainty.; Risk management.; Decision making -- Mathematical models.; elektronické knihy; electronic books